Integrasi Media Alam dalam Pembelajaran IPS di Sekolah Dasar untuk Menumbuhkan Kesadaran Sosial dan Ekologis Siswa - Raziska Ibrahimi (FKIP UNSULTRA, 2025)
Social Studies (IPS) learning in elementary schools plays a crucial role in shaping students' character and concern for the social and natural environment. This study aims to examine various literature on the use of natural media in social studies learning to foster students' social and ecological awareness. Natural media, such as soil, water, plants, rocks, and the environmental conditions around the school, serve not only as learning aids but also as a means to instill the values of social empathy, responsibility, and environmental preservation. This literature review was conducted by reviewing 25 relevant scientific articles, reference books, and research reports published between 2018 and 2024. The results of the study indicate that the use of natural media in social studies learning contextually and thematically can improve students' understanding of the relationship between humans and their environment, strengthen students' emotional involvement in social and ecological issues, and encourage students to actively participate in concrete actions to protect the environment. In addition, natural media strengthens experiential learning, which supports the achievement of the Independent Curriculum competencies. This study recommends that teachers design integrative and reflective learning strategies based on natural media to create a generation with social and ecological awareness.